Using wavelet-based method for detection of atrial late potentials and ECG classification - Ivanushkina, N. G.; Ivan’ko, E. O.; Fesechko, V. A.; Dorosh, N. V. (Видавництво Львівської політехніки, 2010)
The wavelet-based method is proposed to improve detection of low-amplitude components of P wave. Atrial Late Potentials are simulated by solving the Hodgkin-Huxley Equations. Classification of ECG is accomplished by cluster analysis of wavelet coefficients.
Keywords: arrhythmia; atrial Late Potentials; high - resolution ECG; wavelet transform; cluster analysis